(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article aims to arouse children’s interest and interest in fiction, to teach them to feel the charm of fiction, to develop children’s interest and love for fiction, to give them a sense of beauty and beauty in art.